Pengaruh bahasa gaul terhadap remaja kristen masa kini - Dedi Dedi; Martinus Sulang; Presi Nilasari (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2024)
The use of slang today is very influential on Christian teenagers, and has a complex impact, depending on the context and how it is used. In Christian circles we need to use language that can be understood and understood. Christian teens may feel the need to use slang to feel more connected to their peers. Language is a part of culture. Slang is typical teenage language, the words are changed in such a way, so that it can only be understood among them, it can be understood by almost all Christian teenagers who are reached by the mass media, even though these terms develop, change and increase almost every day. Slang is a language that has unique terms, while the second definition makes it clearer that those who use this language are teenagers and this language will continue to develop. The characteristics of slang, the factors supporting the rise of slang among Christian teenagers, the influence of slang on everyday language and the impact of the use of slang today.